Surface integrity and fatigue performance of GH4169 superalloy using abrasive belt grinding. (December 2022) - Xiao, Guijian; Chen, Benqiang; Li, Shaochuan; Zhuo, Xiaoqin; Zhao, Zeyong
Highlights: The influence of abrasive belt grinding process parameters on surface roughness and residual stress was studied by exploring grinding experiment. Four groups of abrasive belt grinding process parameters were selected to process fatigue samples, and the effects of process parameters on grinding force, grinding heat, surface morphology, roughness and residual stress were discussed in detail. The influence of process parameters on fatigue performance was discussed by means of surface integrity. The range of processing parameters to ensure grinding efficiency and high service performance is obtained. Abstract: GH4169 superalloy is the key material for advanced aero-engine high-temperature blades. Improving the surface integrity of the GH4169 superalloy after machining is conducive to improving fatigue performance, which is of great significance for the long-term stable service of the aero-engine. Abrasive belt grinding can effectively improve the surface integrity of GH4169, but the influence of surface integrity on fatigue performance after belt grinding with different process parameters has not been fully revealed. The grinding experiments on the influence of different process parameters on GH4169 surface integrity were carried out, and the influence of process parameters on surface morphology, roughness, and residual stress was explored. On this basis, fatigue experiments were carried out on the samples processed with typical process parameters at 80 % yield strength. The influence of process parameters on fatigue performance was discussed in combination with the surface integrity and cross-section of four groups of samples. The results show that different abrasive belt grinding process parameters can significantly change the surface morphology, roughness, residual stress, and other surface integrity indexes. Roughness mainly affects stress concentration. Macroscopically, the greater the roughness is, the easier crack initiation is. Sample 3 with the smallest roughness is 111.04 % higher than Sample 1. The residual stress can inhibit crack initiation and slow crack propagation. Even under large roughness, the fatigue life of Sample 4 is still better than that of Sample 1, and the stable propagation rate of Sample 4 is 32.4 % slower than that of Sample 3. Considering the anti-fatigue performance and processing efficiency, the linear speed range is 11 to 15 m/s, the feed speed range is 5 to 9 mm/s, and the grinding depth is 0.1 to 0.25 mm.